Kepuasan Kerja Dipengaruhi oleh Kompensasi, Motivasi dan Disiplin Kerja pada Karyawan PT. Sukses Bersama Akmal - Brian Leonardo Oslan,; Syahril Hasan,; Tutik Yuliani, (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this study was to determine the effect of Compensation, Motivation, and Work Discipline on Employee Job Satisfaction at PT. Sukses Bersama Akmal. The type of research used is quantitative research. The sampling technique in this study is purposive sampling with the number of employee population, so only a portion of the sample is taken to represent the population of PT. Sukses Bersama Akmal, which is 65 permanent employees. The data collection method is carried out by distributing questionnaires. This study uses multiple linear regression with the help of SmartPLS in processing data. The results of this study indicate that the variables of compensation, motivation and work discipline have an influence on employee job satisfaction at PT. Sukses Bersama Akmal.